1990
DOI: 10.1152/jn.1990.64.4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory responses of single neurons in the caudolateral orbitofrontal cortex of the macaque monkey

Abstract: 1. In recordings made from 3,120 single neurons, a secondary cortical taste area was found in the caudolateral part of the orbitofrontal cortex of the cynomolgus macaque monkey, Macaca fascicularis. The area is part of the dysgranular field of the orbitofrontal cortex and is situated anterior to the primary cortical taste areas in the frontal opercular and adjoining insular cortices. 2. The responses of 49 single neurons with gustatory responses in the caudolateral orbitofrontal taste cortex were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(180 citation statements)
references
References 31 publications
7
170
1
2
Order By: Relevance
“…Rolls et al (1990) reported that only 49 (1.6%) of 3120 cells within BA 12o responded to taste. Thorpe et al (1983) have explored more medially, near the regions described in this study, and found 39 (7.9%) taste cells within a sample of 494 neurons recorded from BAs 13a, 13m, and 13l.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rolls et al (1990) reported that only 49 (1.6%) of 3120 cells within BA 12o responded to taste. Thorpe et al (1983) have explored more medially, near the regions described in this study, and found 39 (7.9%) taste cells within a sample of 494 neurons recorded from BAs 13a, 13m, and 13l.…”
Section: Discussionmentioning
confidence: 99%
“…This high proportion does not result from our having used vastly different stimulus concentrations or a less stringent response criterion than those of previous investigators. The concentrations of glucose and QHCl in our basic stimulus array were the same as those used by SmithSwintosky et al (1991) in the insula and those used by Rolls et al (1990) in the clOFC. We tested 0.3 M NaCl versus the 1.0 M used in the two studies cited above and 0.03 M HCl instead of 0.01 M.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, region G was considered to be the only area with inputs from the thalamic taste nucleus. A third cortical location that is clearly involved in taste has been described more recently after recordings in orbital frontal cortex (OFC) in macaque monkeys encountered neurons responsive to taste substances as well as other stimuli (e.g., Rolls et al, 1989Rolls et al, , 1990Rolls and Baylis, 1994;Rolls, 2000). Neurons in OFC are thought to reflect the hedonic or pleasurable aspects of taste (for reviews, see Kringelbach, 2004;Pritchard and Norgren, 2004).…”
Section: Cortical System For Tastementioning
confidence: 99%
“…7 Neurons in the primary taste cortex do not represent the reward value of taste, that is, the appetite for a food, in that their firing is not decreased to zero by feeding the taste to satiety. 8,9 The secondary taste cortex A secondary cortical taste area in primates was discovered by Rolls et al 10 in the caudolateral orbitofrontal cortex (OFC), extending several millimetre in front of the primary taste cortex. Neurons in this region respond not only to each of the four classical prototypical tastes sweet, salt, bitter and sour, 4,11 but also there are many neurons that respond best to umami tastants such as glutamate (which is present in many natural foods such as tomatoes, mushrooms and milk) 5 and inosine monophosphate (which is present in meat and some fish such as tuna).…”
Section: Introductionmentioning
confidence: 99%